EFFECT OF HEAT TREATMENT ON TOURMALINE FROM BRAZIL - Castañeda C.; Eeckhout S.G.; De Grave E.; da Costa G.M.; Botelho N.F. (My University, 2006)
The crystal-chemical behaviour of tourmaline from Araçuaí, Minas Gerais state, Brazil, when subjected to heating in air atmosphere has been studied by several techniques, including EMPA, UV-Vis, TGA, and Mössbauer spectroscopy. The tourmaline samples are typically intermediate members of the elbaite-schorl series. The origin of colour and of its change after treatment has been discussed in terms of local disorder, presence of metal transition elements, oxidation of ferrous iron at the octahedral site, and simultaneous trap of the excess electron. These findings may be used to enhance the colour in tourmaline crystals or generate wanted colour changes. © Springer-Verlag 2006.
Keywords: COLOUR; CRYSTAL CHEMISTRY; HEAT TREATMENT; TOURMALINE